Bergamottin promotes osteoblast differentiation and bone formation via activating the Wnt/β-catenin signaling pathway. Issue 5 (21st February 2022) - Wang, Xue; Tian, Ye; Liang, Xuechao; Yin, Chong; Huai, Ying; Zhao, Yipu; Huang, Qian; Chu, Xiaohua; Wang, Weisi; Qian, Airong
Abstract : Bergamottin promotes osteoblast differentiation and enhances bone formation by activating the Wnt/β-catenin signaling pathway. Abstract : Osteoporosis is one of the most common bone disorders that seriously affect the health and life quality of elderly individuals. Reduced osteoblast differentiation and bone formation lead to changes in bone volume and microarchitecture, leaving the bones vulnerable to fracture. Bergamottin (BM) is a natural compound derived from various citrus fruits and possesses multiple biological activities including anti-adipogenesis function. This study aimed to evaluate the effects of BM on osteoblast differentiation and its potential anti-osteoporosis capacity, as well as to explore the underlying mechanism. We demonstrated that BM, as a positive regulator for osteogenesis, significantly promoted osteoblast differentiation and bone formation. Mechanically, BM activated the Wnt/β-catenin signaling pathway and promoted the nuclear translocation of β-catenin. In addition, BM dramatically upregulated the expression of β-catenin, enhanced the transcriptional activation of T cell factor 7 (TCF7), and increased the expression of Runt-related transcription factor 2 (Runx2). Taken together, this study revealed that BM enhanced osteoblast differentiation and attenuated ovariectomy (OVX)-induced bone loss, possessing the potential to be developed into a food ingredient or supplement for preventing osteoporosis.